Overcoming the Problem of Appropriation in the Social Market Economy (Economic and Political Thought, 2012)
The creators of the social market economy wanted to formulate a patternof economic policy that would help to achieve effective implementation ofa material goal of the economy without disturbing socially accepted valuessuch as freedom and justice. In their opinion it is possible to achieve thisgoal thanks to the policy of creating an economic order and leaving theeconomic process to the market entities. However, the research conductedby the mainstream economists shows several deficiencies that do not allowit to function fully effectively. One of those deficiencies is the problem ofappropriation, especially its effects. The companies’ desire to maximize profitsmakes those companies give up their investments in case their investments maybe appropriated. That results in a deterioration of economic effectiveness andthe creation of economic rents in some groups of entrepreneurs. The articleis aimed at a closer analysis of the appropriation problem and possibilities ofovercoming it in the social market economy – with the use of means that donot violate its fundamental principles. Moreover, overcoming the problemof appropriation creates opportunities for more effective use of discretionalmeans in the situation of deep economic depression without the violation ofthose fundamental principles.